Clinical utility of miRNA-1, miRNA-29g and miRNA-133s plasma levels in prostate cancer patients with high-intensity training after androgen-deprivation therapy - Gažová, Andrea; Samáková, Adriana; Laczo, Eugen; Hamar, Dušan; Polakovičová, Mája; Juríková, Miroslava; Kyselovič, Ján (Physiological research, 2019)
The randomized trials showed that the addition of training resistance program to androgen-deprivation therapy (ADT) had many beneficial effects for prostate cancer (PC) patients (significant protective effect on the volume of muscle mass) and the studies have revealed a panel of miRNAs, which are deregulate in PC and may serve as promising biomarkers of PC risk. The primary aim of our present study was to investigate the effect of exercise training to changes in body composition (muscle strength) and the secondary endpoint was to investigate the impact of an exercise training program on plasma levels of selected myogenic microRNAs (miRNAs) (miRNA-1, miRNA-29b, and miRNA-133) in PC patients undergoing the ADT. Effect of ADT and exercise intervention showed significant increase (experimental group vs. control group) the changes in body composition, free testosterone levels, IL-6 and plasma levels of myogenic miRNAs and significant reduced insulin serum levels. In conclusion, resistance training with ADT in the treatment of PC significantly changed the physical and metabolic function and the plasma levels of specific myogenic miRNAs. Our data support with the other publicized results.
Keywords: odporový trénink; Prostatic Neoplasms; Resistance Training; nádory prostaty; Aged; Androgen Antagonists; mikro RNA; Humans; mužské pohlaví; senioři; lidé; prospektivní studie; lidé středního věku; antagonisté androgenů; Male; Middle Aged; MicroRNAs; Prospective Studies